The Measurement of Central Bank Autonomy : Survey of Models, Indicators, and Empirical Evidence - Laurens, Bernard (IMF Working Papers; Working Paper ;, 2006)
This paper presents a survey of the literature on the measurement of central bank autonomy. We distinguish inputs that constitute the building blocks in the literature, and the literature that builds on them. Issues including sensitivity analysis, robustness, and endogeneity are discussed. The review shows that empirical evidence regarding the beneficial effects of central bank autonomy is substantial, although some technical issues still remain for further research. In particular, central bank autonomy raises the issue of subjecting the monetary authorities to democratic control; this calls for additional research on the linkages between central bank autonomy and accountability and transparency. Additional empirical analysis on the relationship between the financial strength of the central bank and its de facto autonomy, and between its autonomy and financial stability, would also be desirable.